2006
DOI: 10.1177/021849230601400514
|View full text |Cite
|
Sign up to set email alerts
|

Multinodular Goiter Compressing the Trachea following Open Heart Surgery

Abstract: Acute hemorrhage into an adenomatous goiter following cardiac surgery is a rare cause of acute upper airway obstruction. We report an unusual presentation of respiratory distress in a patient with goiter recovering from open heart surgery, which was successfully treated by left hemithyroidectomy. A mandatory evaluation of the upper trachea in patients with long-standing benign goiter is recommended prior to cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
(3 reference statements)
0
15
0
1
Order By: Relevance
“…With respect to the risk factors for acute airway obstruction, studies have suggested that acute obstruction is due to sudden hemorrhage into a cyst, an upper respiratory tract infection causing edema, tracheal collapse or worsening of comorbidities (5,8,10,11). Since the patient in our case was asymptomatic, it was decided not to operate immediately.…”
Section: Discussionmentioning
confidence: 90%
“…With respect to the risk factors for acute airway obstruction, studies have suggested that acute obstruction is due to sudden hemorrhage into a cyst, an upper respiratory tract infection causing edema, tracheal collapse or worsening of comorbidities (5,8,10,11). Since the patient in our case was asymptomatic, it was decided not to operate immediately.…”
Section: Discussionmentioning
confidence: 90%
“…Sajja et al 9 reported a case of intrathyroidal haemorrhage causing respiratory failure shortly after cardiac valve replacement surgery in a 60-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
“…Acute airway obstruction due to rapidly enlarging goitre could occur following cardiac operation with cardiopulmonary bypass [17,18]. Cardiopulmonary bypass compromises the upper airway by initiating series of inflammatory responses which ultimately lead to systemic tissue oedema including acute enlargement of the thyroid gland [19,20].…”
Section: Should Thyroidectomy and Cabg Performed Concurrently?mentioning
confidence: 99%